Toward the upscaling of school nutrition programs in Dubai: An exploratory study - AlGurg, Reem; Abu Mahfouz, Nour; Otaki, Farah; Alameddine, Mohamad (Frontiers in Public Health, 2022)
Abstract Background School nutrition programs impact the intellectual, social, and emotional development of school children, as well as their future risk of developing Non-Communicable Diseases. While many stakeholders are involved in the development, implementation, and evaluation of school nutrition programs in Dubai, United Arab Emirates, little is known about the complementarity among those stakeholders, and the means to upscale school nutrition programs while ensuring effective, efficient, and equitable implementation. Accordingly, this study aims at exploring the perceptions of a diverse group of stakeholders, positioned at differing levels of the public health and education ecosystems in the United Arab Emirates, in relation to current guidelines and practices around the planning, implementation, and evaluation of school nutrition programs in Dubai, United Arab Emirates. Methods The study relied on a qualitative design, based on semi-structured key informant interviews. A total of 29 interviews were carried-out. Those interviewees included leaders and directors from different institutions, decision- and policy- makers, nutritionists, school nurses and nurse managers, and school principals and vice principals. All stakeholders were interviewed by the research team. Data was transcribed, and then thematically analyzed using the health systems’ model as an analytic framework. Results The thematic analysis of interview data identified five interrelated themes. The first theme relates to the limited coordination across regulatory local and federal entities, and the multiplicity of guidelines issued by the different stakeholders. The challenges around the human and financial resourcing of school nutrition programs constituted the second theme. The third theme was the weakly coordinated implementation efforts. The fourth theme was the need for better performance measurement, and the fifth theme flagged the need for improved inclusiveness for health needs and cultural preferences of the diverse student body in Dubai. Conclusion This study emphasizes that all the involved stakeholders need to better collaborate to upscale the school nutrition program in Dubai. This will require the formation of a unified governing body, which would identify and develop a single stream of resources, and sets in place a reliable, all encapsulating and equitable implementation plan along with an overarching monitoring and evaluation framework.